Determining The Fees of The Arbitration Panel - Al-Maamari, Abdulwahab Abdullah; Albaraami, Ali Said Ahmed (Syura: Journal of Law, 2024)
The arbitrators' fees are originally determined according to the agreement that may be concluded by both the arbitrator and the arbitrators, provided that the failure of this agreement for any reason does not prevent the arbitration panel from determining its fees according to certain controls, and through this section we will examine the contractual determination of the arbitration panel's fees. As happens in free arbitration, the agreement of the parties and arbitrators regarding determining the fees that these arbitrators will receive in return for performing the arbitration task that will be assigned to them is absent, either due to their negligence, or because one of the arbitrators has been appointed by the court competent for arbitration matters, which naturally means a failure to agree, and in this research we discuss the legal provisions regulating this in Jordanian law with a comparison with some Arab laws, and the research reached the most important results: that in order to guarantee the integrity and objectivity of the arbitrator's determination of his fees alone, the Jordanian and Emirati arbitration law has subjected the arbitrator's decision regarding determining these fees to appeal, and the decision of the competent court of appeal in this regard is final